2021
DOI: 10.1097/aud.0000000000001064
|View full text |Cite
|
Sign up to set email alerts
|

Adult Auditory Brainstem Implant Outcomes and Three-Dimensional Electrode Array Position on Computed Tomography

Abstract: Objectives: Factors contributing to auditory brainstem implant (ABI) outcomes are poorly understood. The aims of this study are to (1) characterize ABI electrode array position on postoperative imaging and (2) determine if variability in position is related to perceptual outcomes.Design: Retrospective cohort study. Subjects were selected from the adult ABI recipient population at Massachusetts Eye and Ear. Postoperative three-dimensional (3D) computed tomography (CT) reconstruction of the head was used to meas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(13 citation statements)
references
References 31 publications
1
12
0
Order By: Relevance
“…For the auditory outcomes reported, the weighted mean recognition for closed-set words was 39.2% (range: 19.6%-83.3%), for open-set words was 23.4% (range: 17.2%-37.5%) and for open-set sentences was 21.5% (range: 2.70%-48.40%) (Figure 2A). 4,7,[10][11][12][13]16,[19][20][21][22][23][24][25][26][27][28]30,33,38,39,42,43,45,51 For 23 reported tumor patients the overall weighted mean CAP score was 3.14 (range: 1.00-3.29): 8.69% had scores of 1, 13.04% had scores of 2, 30.43% had scores of 3, 34.78% had scores of 4, and 8.69% had scores greater than 5.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…For the auditory outcomes reported, the weighted mean recognition for closed-set words was 39.2% (range: 19.6%-83.3%), for open-set words was 23.4% (range: 17.2%-37.5%) and for open-set sentences was 21.5% (range: 2.70%-48.40%) (Figure 2A). 4,7,[10][11][12][13]16,[19][20][21][22][23][24][25][26][27][28]30,33,38,39,42,43,45,51 For 23 reported tumor patients the overall weighted mean CAP score was 3.14 (range: 1.00-3.29): 8.69% had scores of 1, 13.04% had scores of 2, 30.43% had scores of 3, 34.78% had scores of 4, and 8.69% had scores greater than 5.…”
Section: Resultsmentioning
confidence: 99%
“…4,7,16,19,20,24,29,30,32,[39][40][41]44 Direct comparison of tumor and nontumor subjects was done in 13 studies that reported individual patient data for a total of 338 patients (158 tumor and 180 nontumor). 7,8,12,16,19,24,26,30,32,39,40,44,45 The APROSPER score was used to combine auditory outcomes across studies by ranking each audiometric score from 0 to 7 depending upon the difficulty of the test evaluating sound detection, pattern perception, word, or sentence recognition (Table 3). The mean APROSPER score for nontumor subjects was 3.5 (SD: 1.9), and for tumor patients was 3.0 (SD: 2.4), demonstrating that performance is significantly better for nontumor compared to tumor patients when all audiometric tests are combined (t 227 = 2.01, P = .04) (Figure 2B).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Speech recognition appears to be related to duration of deafness, electrode position, and the number of electrodes that produce distinct pitch percepts [ 16 ]. Perceptual outcomes have also been associated with lower levels of electric stimulation [ 35 ]. Better coupling of the ABI to the CNC results in lower stimulation current levels at initial activation [ 24 ], which may reduce non-auditory side effects and provide better perceptual results.…”
Section: Discussionmentioning
confidence: 99%
“…The main problem of electrode shifting is the possible negative effect on perceptual results [ 16 ]. Considering the dimensions of the ABI paddle and the CNC [ 33 , 35 , 37 – 41 ] and the estimated position of the paddle [ 1 , 22 , 42 , 43 ], even a minimal shift could cause undesired non-auditory stimulation [ 1 ]. This also relates to how many electrodes are needed to obtain perceptual results that are comparable to those with CIs.…”
Section: Discussionmentioning
confidence: 99%